Flow control with aerospike behind bluff body - Khan, Sher Afghan; Asadullah, Mohammad; G.M, Fharukh Ahmed.; Jalaluddeen, Ahmed; Baig, Maughal Ahmed Ali (Trans Stellar, 2018)
Flow control in high-speed is challenging due to the high-pressure shock and low-pressure recirculation bubble attached around the vehicle. Wave drag, and Base drag are important accouterments of flow around high-speed objects. This paper deals with base drag, only and presents an experimental study of aerospikes behind the base of bluff bodies to control this drag. A plate of 1 mm thickness with two spikes at 11.5 mm is placed between the nozzle and duct as a passive controller. The Mach numbers deployed for the subsonic regime were 0.6, 0.7 and for transonic regime were 0.8, 0.9 for area ratio 6.25. The L/W ratio taken were 4W, 6W, 8W and 10W. Aerospikes were found to be very effective in controlling base pressure in the transonic regime without influencing the main flow field.